FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - NOVIANTI, VELIA; MARIA, MARIA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to see and examine whether liquidity, leverage, profitability, managerial ownership, institutional ownership, company size, company growth, investment decisions, and tangibility about the influence on firm value. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange during the period 2017 to 2019. This study used a sample selection method, namely purposive sampling, in which 60 companies met the criteria so that 180 data were obtained. The hypothesis of this study was tested and analyzed using multiple linear regression analysis method. The results of this study indicate that liquidity, managerial ownership, firm size, dividend policy, investment decisions, and tangibility have no influence on firm value. Meanwhile, leverage, profitability, and institutional ownership have a positive influence on firm value. The positive influence indicates that an increase in each of these variables will increase firm value. Conversely, company growth has a negative influence on firm value, which indicates that an increase in this variable will decrease firm value